Economic Foundations for Creative Ageing Policy Volume I Context and Considerations - Klimczuk, Andrzej. (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2015)
Ageing populations are a major consideration for socio-economic development in the early twenty-first century. This demographic change is mainly seen as a threat rather than as an opportunity to improve the quality of human life, especially in Europe, where ageing has resulted in a reduction in economic competitiveness. Economic Foundations for Creative Ageing Policy mixes the silver economy, the creative economy, and the social economy to construct positive solutions for an ageing population. Klimczuk covers theoretical analyses and case study descriptions of good practices to suggest strategies that could be internationally popularized.